Environmental impact of sectoral energy consumption on economic growth in Malaysia: evidence from ARDL bound testing approach - Hussain, Hafezali Iqbal; Salem, Milad Abdelnabi; Abdul Rashid, Aimi Zulhazmi; Kamarudin, Fakarudin (Foundation for Enviromental Protection and Research, 2019)
The association of energy utilization with economic progress has always proven to be crucial in modern business. Acknowledging the importance of sectoral energy utilization, the present study explores the environmental impact of industrial, commercial, transportation& agricultural energy consumption on economic progress of Malaysia. Applying the functionality of Cobb-Douglas, the authors utilized the long time series data from the period of 1978 to 2016. The outcomes of the empirical investigations using ARDL bound testing approach ascertain the presence of long-run association between GDP growth, capital, labor along with the sectoral energy utilizations of the country. Furthermore, the study also finds empirical evidences of positive significant associations of all energy consumptions with economic growth. Lastly, the results of Granger-causality also confirm the existence of bi-directional causal association between all sectoral energy consumptions and Malaysian economic progress. This study brings a valid policy recommendation for the Malaysia Government to invest more in all sector of energy for the progress in the Malaysian economic growth.